"Back There We Had Nothing to Eat": The Case of Transnational Food Insecurity. (August 2017) - Carney, Megan A.
Abstract: This article discusses migrant food insecurity in the United States from the perspective of Mexican and Central American migrant women. Many describe migrating because they had nothing to eat in their countries of origin. Migration is thus framed as a necessary strategy for overcoming food insecurity. I argue that these women's perspectives are unique in the migration literature because food security comprises a gendered labour from which men are frequently spared. Unfortunately, food insecurity still prevails in these women's households in the US. Assuming a "double‐duty" workday of earning wages and overseeing care within households, these women experience the added burden of ensuring food security of households "back there." Thus, I argue that the food practices of Mexican and Central American migrant women provide a unique lens through which to understand the increased feminization of transnational migration from Latin America to other regions of the world.